Analysis Of The Influence Of Ship Speed On Seakeeping Motion On The Ship - Riyadh, Muhammad; Syaifullah. A, Muh. (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2023)
Ship motion (Seakeeping) is the ability of a ship to survive under any conditions. Therefore this capability is clearly an important aspect in terms of ship design (Ship Design). The shape of the hull greatly influences the characteristics of the movement and operability of the ship itself. Vessel operability is the amount of time at sea during which the structure can still operate according to established criteria and its correlation to the height at which the weather will occur. In this study, an analysis of 3 degrees of freedom of translational movement and heave roll and pitch rotation was carried out on the model of a fast ship type planing hull at regular waves with parameters of body mass, radius of gyration, damping and others presented in the form of Response Amplitude Operator (RAO) images.